The clinical presentation caused by truncating CHD8 variants. Issue 1 (14th May 2019) - Douzgou, Sofia; Liang, Hui Wen; Metcalfe, Kay; Somarathi, Suresh; Tischkowitz, Marc; Mohamed, Wafik; Kini, Usha; McKee, Shane; Yates, Laura; Bertoli, Marta; Lynch, Sally Ann; Holder, Susan; et al.
Abstract: Variants in the chromodomain helicase DNA‐binding protein 8 (CHD8) have been associated with intellectual disability (ID), autism spectrum disorders (ASDs) and overgrowth and CHD8 is one of the causative genes for OGID (overgrowth and ID). We investigated 25 individuals with CHD8 protein truncating variants (PTVs), including 10 previously unreported patients and found a male to female ratio of 2.7:1 (19:7) and a pattern of common features: macrocephaly (62.5%), tall stature (47%), developmental delay and/or intellectual disability (81%), ASDs (84%), sleep difficulties (50%), gastrointestinal problems (40%), and distinct facial features. Most of the individuals in this cohort had moderate‐to‐severe ID, some had regression of speech (37%), seizures (27%) and hypotonia (27%) and two individuals were non‐ambulant. Our study shows that haploinsufficiency of CHD8 is associated with a distinctive OGID syndrome with pronounced autistic traits and supports a sex‐dependent penetrance of CHD8 PTVs in humans. Abstract : Variants in the chromodomain helicase DNA‐binding protein 8 (CHD8) have been associated with intellectual disability (ID), autism spectrum disorders (ASD) and overgrowth and CHD8 is one of the causative genes for OGID (overgrowth and ID). We investigated 25 individuals with CHD8 protein truncating variants (PTVs), including 10 previously unreported patients and found a male to female ratio of 2.7:1 (19:7) and a pattern of common features: macrocephaly (62.5%), tall stature (47%), developmental delay and/or intellectual disability (DD/ID, 81%), autism spectrum disorders (ASD, 84%), sleep difficulties (50%), gastrointestinal problems (40%), and distinct facial features. Most of the individuals in this cohort had moderate‐to‐severe intellectual disability, some had regression of speech (37%), seizures (27%) and hypotonia (27%) and two individuals were also non‐ambulant. Our study shows that haploinsufficiency of CHD8 is associated with a distinctive OGID syndrome with pronounced autistic traits and supports a sex‐dependent penetrance of CHD8 PTVs in humans.